Pola Kemampuan Berpikir Kreatif Ditinjau dari Gender Siswa Sekolah Menengah dalam Pembelajaran IPA - Alifia Kurnia; Sukarmin; Widha Sunarno (Risenologi, 2021)
This study aims to analyze the initial profile of the creative thinking ability of junior high school students in science by gender. This research is a quantitative descriptive method with data collection techniques through giving open-ended tests based on creative thinking indicators that have been validated by expert and testing the validity of items using the Karl Person product moment correlation coefficient formula. Reliability testing using the Alpha formula. The sample in this study were 5 classes from SMP Negeri 15 Surakarta with a total of 150 students consisting of 75 female students and 75 male students. The results of this study indicate that the pattern of creative thinking abilities of Junior High School students varies by gender based on the four indicators of Fluency, Flexibility, Originality, Elaboration. Based on data analysis, it shows that the creative thinking ability of female students is higher than that of male students.